Effects of Natural Substances on Healing of Long Bone Fractures: A Narrative Review of Traditional Persian Medicine: - Sadeghi, Seyed Mohammad Hasan; Heydarirad, Ghazaleh; Hosseini Khameneh, Seyed Mehdi; Khodadoost, Mahmood; Kamalinejad, Mohammad; Jafari, Shirin; Gachkar, Latif (Galen Medical Journal, 2016)
Fractures, especially leg fractures, are one of the most common problems in the world, and it causes a considerable economic and social burden for patients and societies. Orthopedic surgery plays the most important role in the treatment of fractures, but it is expensive and requires anesthesia which has a variety of side effects. Besides surgery and conventional treatments, it seems that the use of natural substances as complementary therapy can be useful. In Traditional Persian Medicine (TPM) manuscripts, many diverse natural substances, especially medicinal herbs, are mentioned as useful medications for fracture healing. The aim of this study was to investigate medicinal plants and natural substances used in TPM as useful in fracture healing, by an overview of traditional knowledge as compared with new investigations. The main manuscripts of TPM, including the Canon of Medicine, Tohfat-ol-Moemenin, Exir-e–azam and Makhzan-ol-advieh, were assembled through a literature search, to select the substances used in fracture healing. Also, current evidence on related substances were studied through a search of Google Scholar and PubMed databases. In this study, eleven substances were identified and categorized into three groups: plants, animals, and minerals. The results of our study showed that the most cited substances were used due to their effects on fracture or wound healing, inflammations, and pain. This historical assessment can help in obtaining new data about natural substances for faster fracture healing, which may lead to subsequent opportunities to assess their potential medicinal use. [GMJ. 2016;5(4):165-72]